Kinetic and kinematic features of countermovement and sauté jumps in classical ballet dancers - Diehl, M.; Exell, J. S.; Cunha, S. A. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate how the external rotations of lower limbs influence the performance of ballet dancers in jumps. Four ballet dancers with high technical proficiency were recruited for a test, they performed three attempts the countermovement and sauté jump. Two force plates were used to determine ground reaction forces. Six cameras were used to collect the kinematic data. It was analyzed the peak of knee flexion, peak of ground force reaction and jump height. The performance in countermovement and sauté jump tests was compared through box plot analysis. In conclusion, even with a lower degree of knee flexion, dancers can produce higher jumps and more ground force reaction on countermovement jump. The results suggest that the attention focus when jumping is an important determinant of jump performance.